CITY AS AN OBJECT OF MULTIDIMENSIONAL LINGUISTIC RESEARCH - Vyacheslav I. Terkulov (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2025)
The work introduces the description of basic directions for a comprehensive study of a city as a linguistic entity: the onomastic direction, primarily aimed at revealing the linguacultural essence of the city name, and the linguistic proper, that determines the peculiarities of the lexicon, thesaurus and pragmaticon of the city and the linguistic personality of the city dweller as a character and the agent of the city text. The work uses a comprehensive methodology. It includes onomastic techniques, in particular techniques for determining the etiology and the origins of onyms, and linguistic techniques of continuous sampling, comparison, distributional and component analysis. As an example, the article describes the peculiarities of astionym analysis: its documentary and folklore syntagmatics, regarded as textual representation of territorial border determination, and paradigmatics, that reveals the specifics of its creation, reasons, and means of renaming (diachronic), formal and semantic variability in functioning at the current state of language development (synchronous). The study describes the means of personality identification and self-identification formation, which includes the use of the katoikonym, regarded as individual’s regiolect features of speech. The paper gives a general definition to regional linguaculturemes: the local and the general-language ones. Application prospect of the research results is the creation of regional dictionaries: Associative Dictionary of Donbass, Dictionary of Donetsk Colloquialism, Dictionary of Miner’s Slang, Dictionary of Donetsk Urbanonyms, Dictionary of Names of Donbass Cities, Dictionary of the Language of the Civil War in Donbass 2014–2021, Dictionary of Poetic Concepts in Donbass and Mental Map of the City of Donetsk. It is proposed to further describe the urbanonymicon of the city, the system of urban linguaculturemes, linguaculturemes of the war language, the peculiarities of languages functioning on the territory of Donetsk and the features of Donetsk texts.